An Intelligent Controller Design for Magnetorheological Damper Based on a Quarter-car Model - Tusset, Angelo Marcelo; Rafikov, Marat; Balthazar, José Manoel [UNESP] (Sage Publications Ltd, 2009)
This paper presents the control strategies of nonlinear vehicle suspension using a magnetorheological (MR) damper. We used two different approaches for modeling and control of the mechanical and electrical parts of the suspension systems with the MR damper. First, we have formulated and resolved the control problem in order to design the linear feedback dumping force controller for a nonlinear suspension system. Then the values of the control dumping force functions were transformed into electrical control signals by the application of a fuzzy logic control method. The numerical simulations were provided in order to show the effectiveness of this method for the semi-active control of the quarter-car suspension.
Keywords: Nonlinear vehicle suspension system; magnetorheological damper; linear feedback controller; fuzzy logic controller